Police-Public Contact Survey, 2002 (United States) ([Verlag nicht ermittelbar], 2005)
The Police-Public Contact Survey (PPCS), was designed by the Bureau of Justice Statistics (BJS) to document contacts between police and the public that culminated in police using force. The 2002 survey was conducted as a supplement to the National Crime Victimization Survey (NCVS). To date, the PPCS has been conducted three times by BJS. The first survey -- described in the BJS publication, "Police Use of Force: Collection of National Data" (NCJ 165040) -- documented levels of contacts with police during 1996. The second survey -- described in "Contacts Between Police and the Public: Findings from the 1999 National Survey" (NCJ 184957) -- recorded police-citizen contacts in 1999. These data are archived in POLICE-PUBLIC CONTACT SURVEY, 1999: [UNITED STATES] (ICPSR 3151). The third survey -- described here under the title "Contacts Between Police and the Public: Findings From the 2002 National Survey" (NCJ 207845) -- covered interactions between police and the public in 2002. The results of this survey are contained in this data collection.